Portable FMCW ground penetrating radar - I. Yu. Malevich; A. S. Lopatchenko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The results of the design of a portable FMCW ground penetrating radar is considered. The results of experimental studies of the device are presented.